2023
DOI: 10.1093/geroni/igad021
|View full text |Cite
|
Sign up to set email alerts
|

Queer Aging: Older Lesbian, Gay, and Bisexual Adults’ Visions of Late Life

Abstract: Background and Objectives Diversity in aging has received increased attention in recent years in the field of gerontology. However, older lesbian, gay, and bisexual (LGB) people have largely been missing from these conversations. In this study, I examine older LGB people’s subjective views on the aging process, focusing specifically on visions of late life. Research Design and Methods Life story interviews were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Moreover, the historically-contingent personal, social, and community relationships that lesbians and gay men form likely vary more widely and come into play at later points in the life course than they do among heterosexuals, whose sexual identities are typically formed in late childhood and young adulthood, and typically (although not always) remain the same over subsequent years. As Miller (2023 , p. 2) recently wrote, ‘LGB [lesbian, gay, and bisexual] people have not historically met heterosexual-centric markers of adulthood (i.e., marriage, childrearing) and, in other cases, these major life events were delayed until fairly recently’. Thus, ‘the’ life course plays out differently in gay contexts, enmeshed as it is in ‘queer temporalities, where cultural narratives provide for alternative articulations of life courses, futures, and ageing, away from “straight time”’ ( Sandberg and King, 2022 : 4).…”
Section: Core Concepts and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the historically-contingent personal, social, and community relationships that lesbians and gay men form likely vary more widely and come into play at later points in the life course than they do among heterosexuals, whose sexual identities are typically formed in late childhood and young adulthood, and typically (although not always) remain the same over subsequent years. As Miller (2023 , p. 2) recently wrote, ‘LGB [lesbian, gay, and bisexual] people have not historically met heterosexual-centric markers of adulthood (i.e., marriage, childrearing) and, in other cases, these major life events were delayed until fairly recently’. Thus, ‘the’ life course plays out differently in gay contexts, enmeshed as it is in ‘queer temporalities, where cultural narratives provide for alternative articulations of life courses, futures, and ageing, away from “straight time”’ ( Sandberg and King, 2022 : 4).…”
Section: Core Concepts and Approachmentioning
confidence: 99%
“…However, most gay aging researchers who consider historical context explicitly focus on generations ( Lyons et al, 2015 ; Ramirez-Valles, 2016 ; Halkitis, 2019 ; Fredriksen-Goldsen et al, 2023 ), with some (e.g., Hammack and Cohler, 2011 ; Hammack et al, 2019 ; Bitterman and Hess, 2021 ) problematically using the terms generation and cohort interchangeably, and most trace historical factors shaping sexual identity development (see, e.g., Hammack et al, 2018 ; Bishop et al, 2020 ) rather than such concrete later-life circumstances as income. Far fewer have used the life course perspective to consider older gay men’s concrete circumstances or to explore cumulative disadvantage in these older populations (but see, e.g., Westwood et al, 2020 ; Miller, 2023 ).…”
Section: Lesbian and Gay Aging Researchmentioning
confidence: 99%
“…It is widely documented that older sexual minorities experienced rejection from families of origin (Weston, 1991). Due to historical exclusion from the institutions of marriage and family, older sexual minorities are also more likely to be single and without children of their own (Fredriksen-Goldsen et al, 2015;Miller, 2023).…”
Section: Caregivingmentioning
confidence: 99%
“…It is widely documented that older sexual minorities experienced rejection from families of origin (Weston, 1991). Due to historical exclusion from the institutions of marriage and family, older sexual minorities are also more likely to be single and without children of their own (Fredriksen‐Goldsen et al., 2015; Miller, 2023). Consequently, unlike heterosexual individuals who often rely on children and extended family to care for them, sexual minorities often lack informal caregivers; roughly 20% of older gender and sexual minorities have reported that they are unsure who will provide care for them when they are in need (MetLife Mature Market Institute, 2010).…”
Section: A Life Course Perspective On Older Sexual Minoritiesmentioning
confidence: 99%
“…Prior sociological research notes how these disparities derive from existing sociopolitical conditions 1 University of South Florida, Tampa, FL, USA whereby TGNB Americans endure widespread stigma, discrimination, and violence over the life course-problems that engender major psychosocial challenges for TGNB people as they access and utilize health services (Lampe et al, 2023;Sumerau and Mathers, 2019). Prolonged exposures to these stressors often exacerbate the need for gender-affirming care services, providers, and resources among TGNB patients (Clark et al, 2018;Miller, 2023). This is especially the case for TGNB youth and young adults, a medically underserved population with limited financial security and legal protections in the United States (Ashley, 2019;Robinson and Schmitz, 2021).…”
Section: Introductionmentioning
confidence: 99%